347 Nephrology research – understanding educational support surrounding chronic kidney disease (CKD) – patient and allied health professional (AHP) perspectives. (17th August 2022) - Muhammad, Shahid
Abstract : Aims: This UK study seeks to understand Educational Support surrounding CKD. Methods: This research used Qualitative Methodology, and theoretical framework involved an Inductive Content Analysis (ICA) approach which is particularly effective to help understand analysis in linking theory, or framework ( figures 1 and 2 ). Patient and Public Involvement (PPI): Two workshops took place in May and June (2019) wherein topic tagging activities were co-developed between the Renal Patient Support Group (RPSG) and the Kidney Disease and Renal Support Groups (KDARs) for Kids platforms. Sampling and Recruitment: 19 participants between 4 cohorts, that included 6 General Practitioner (GPs), 4 Healthcare Scientists (HS), and 6 CKD Patients (CKDPs) were recruited and participated in telephone interviews. Data Collection: Topic guides were developed for participant cohorts with several themes to collect data through one-to-one telephone interviews Results: Analysis: NViVo-12 software provided opportunity to code and glean insight to develop overall conclusions. Results: Nine (9) main themes and several sub-themes were identified when coding for HPs, and Nine (9) main themes and several sub-themes identified when coding qualitative data for CKDPs. Conclusion: Conclusion: There needs to be a coordinated effort between patients and professionals, to understand how CKD education should be more integrated at point of care, and public health.